2017
DOI: 10.1021/acsnano.6b06842
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Transfer of an Ultralong and Seamless Nanowire Array Crystallized at High Temperature for Use in High-Performance Flexible Devices

Abstract: Nanowire (NW) transfer technology has provided promising strategies to realize future flexible materials and electronics. Using this technology, geometrically controlled, high-quality NW arrays can now be obtained easily on various flexible substrates with high throughput. However, it is still challenging to extend this technology to a wide range of high-performance device applications because its limited temperature tolerance precludes the use of high-temperature annealing, which is essential for NW crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 38 publications
(51 reference statements)
0
33
0
Order By: Relevance
“…In addition, the peak open circuit voltage and peak short circuit current levels at resonant frequency, measured for the BaTiO 3 NW based NEMS energy harvester, were found to be more than five times greater than the response recorded from a ZnO‐based NEMS energy harvester (Figure 7f,g). Seo et al also reported a high‐performance energy harvester using a laterally aligned ultralong BaTiO 3 nanowire array 139. By developing a nanotransfer method that can include a high‐temperature annealing process during the transfer, they successfully demonstrated a perfectly aligned and ultralong (≈2 cm) BaTiO 3 nanowire array on a flexible PET substrate (Figure 7h–l).…”
Section: High‐performance Nems/mems Devicesmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the peak open circuit voltage and peak short circuit current levels at resonant frequency, measured for the BaTiO 3 NW based NEMS energy harvester, were found to be more than five times greater than the response recorded from a ZnO‐based NEMS energy harvester (Figure 7f,g). Seo et al also reported a high‐performance energy harvester using a laterally aligned ultralong BaTiO 3 nanowire array 139. By developing a nanotransfer method that can include a high‐temperature annealing process during the transfer, they successfully demonstrated a perfectly aligned and ultralong (≈2 cm) BaTiO 3 nanowire array on a flexible PET substrate (Figure 7h–l).…”
Section: High‐performance Nems/mems Devicesmentioning
confidence: 99%
“…Recently, a method of transferring nanowire arrays to a flexible substrate using physical force has been developed. After deposition of the sacrificial layer and the nanomaterials sequentially on the protruding portion of the nanograting patterns, hook‐shaped nanowires were formed by selective etching of the sacrificial layer 73,139. By forming a mechanically interlocking structure by filling a soft material on the hooked structure, various materials could be transferred regardless of the chemical nature of these substances.…”
Section: Fabrication Of Geometrically Structured Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A piezoelectric energy harvester is one of the ways to harvest mechanical energy, which has been widely investigated by many researchers [18][19][20][21][22][23][24][25][26][27][28][29][30]. When a piezoelectric device is deformed by an external mechanical stress, a dipole moment is changed inside the piezoelectric material, and thereby an electric charge is generated [31][32][33][34][35][36][37]. Although inorganic ceramics such as a lead zirconate titanate (PZT) or organic polymers such as polyvinylidene fluoride (PVDF) were widely used as active materials of energy harvesters, but the brittle nature and the thick thickness or the low piezoelectric coefficient caused limitations in the various applications [38][39][40][41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the flexible electronic system on a polymer substrate can be obtained in a final delamination step after removal of the sacrificial layer via a wet etching process. However, this method is inefficient and usually takes tens of minutes to few hours, as limited by slow reaction and diffusion . In addition, dissolution of an inorganic layer normally requires harsh etchants (e.g., HF, HNO 3 , NaOH, etc.)…”
mentioning
confidence: 99%